2014
DOI: 10.1080/07315724.2013.827065
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometry, Nutritional Status, and Dietary Intake in Pediatric Patients with Osteogenesis Imperfecta

Abstract: This study showed that stature was compromised mainly in OI type III. Skinfold thickness and arm circumference correlated to nutritional status and also to body fat calculated by DEXA. Daily calcium intake was below the recommended levels in pediatric patients with OI. These findings are important for the management of OI subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 40 publications
5
24
1
1
Order By: Relevance
“…The mean Ht SDS in both OI-III and OI-IV was below -2.5 SDS with a significant difference between OI-I and both OI-III and OI-IV, while a nonsignificant difference was detected between OI-III and OI-IV (p = 0.21). Our results of length and Ht SDSs in OI patients were in agreement with other studies [10,26,27,28] which found that many patients with OI-I and few with OI-IV had a Ht SDS within the reference interval, in contrast to those with OI-III who were mostly shorter than reference ranges.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The mean Ht SDS in both OI-III and OI-IV was below -2.5 SDS with a significant difference between OI-I and both OI-III and OI-IV, while a nonsignificant difference was detected between OI-III and OI-IV (p = 0.21). Our results of length and Ht SDSs in OI patients were in agreement with other studies [10,26,27,28] which found that many patients with OI-I and few with OI-IV had a Ht SDS within the reference interval, in contrast to those with OI-III who were mostly shorter than reference ranges.…”
Section: Discussionsupporting
confidence: 82%
“…Although growth deficiency is a key feature of severe OI and a frequent feature of mild to moderate forms of the disease [11], studies on systematic anthropometric assessment of OI children are scant [26]. Thirty-three percent of our OI cases were short, most of whom had type OI-III.…”
Section: Discussionmentioning
confidence: 99%
“…was found between being overweight/obese and OI type, with a higher percentage of energy intake and obesity in OI type III compared to types I and IV (23,24).…”
mentioning
confidence: 82%
“…It is also possible that patients with OI plateau in their growth due to the condition itself-i.e., a chronic disease with increased caloric needs for appropriate linear growth. In a recent study examining patients' energy requirements, OI type III had a higher percentage of energy intake, possibly indicating an increased caloric need (24). The obesity that develops over time could simply be a result of the sedentary lifestyle that is a result of the condition, which is typified by recurrent fractures, pain, skeletal abnormalities, and severe scoliosis with resultant wheelchair dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation